The Influence of Work Culture on Employee Commitment at The Binjai City Regional Secretariat Office - Herdalina Pardede, Eva; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
The aim of this research is to determine and analyze the influence of Work Culture on Work Commitment at the Binjai City Regional Secretariat Office. This research was conducted using a causal associative quantitative approach. The sample used was all employees with ASN status with a total of 82 people taken using proportional sampling. The research results show that Work Culture has a positive and significant effect on Work Commitment. This is shown by the T-count value of T-count of 44.054 > t table 1.66412, with a significance value of 0.000 < 0.05. The regression coefficient shows that if Work Culture is increased by 1 unit, then Work Commitment will increase by 0.957 units assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.960 or 96.00%, which indicates that Work Culture has a very high influence on Work Commitment, while the remaining 4.00% is influenced by other factors that have not been studied. Thus, partially, Work Culture has a positive and significant effect on Work Commitment at the Binjai City Regional Secretariat Office. This identifies that improvements in Work Culture can contribute to increased Work Commitment.